Role of the advanced nurse practitioner within the vascular team: A qualitative study of vascular physicians and nurses - Kubiak, Thibaut; Sitruk, Jonas; Durivage, Andréanne; Khider, Lina; Mohamedi, Nassim; Détriché, Grégoire; Messas, Emmanuel; Mirault, Tristan; Goudot, Guillaume (Frontiers in Public Health, 2023)
Objective: To assess the perception of Advanced Nurse Practitioners (ANP) by physicians and nurses in vascular medicine. As the status of ANP in France was recently enacted by law in 2018, we aim to investigate physicians and nurses working with patients suffering from Peripheral Arterial Disease (PAD) to gather their opinions and draw the cooperation outlines these practitioners could have with an ANP. Methods: Qualitative study based on in-depth interviews conducted among healthcare practitioners taking care of patients with PAD: 10 physicians working either in a private practice setting or hospital setting or both, and 8 nurses working within a hospital inpatients vascular unit. Verbatim responses were extracted and coded according to a continuous thematization method. Results: Three main features emerged from participants’ responses. Vascular medicine has a specific organization with a significant lack of time and staff to fulfill the mission regarding patients’ severity of illness. Second, the ANP is wanted to fill part of this gap. The expected benefits include a smoother care pathway and increased capacity for cardiovascular education and prevention, especially during consultations. Lastly, some clarification is required to integrate such new practitioners within vascular teams already in place. Conclusions: ANP could be the missing link in a ‘Vascular team’ by creating a continuum in the care of patients with PAD, ensuring clinical assessment, nursing supervision, adverse event screening, and renewing drug prescriptions with the required adaptations while ensuring an essential part of therapeutic education adapted to each patient.